Vortioxetine exerts anti‐inflammatory and immunomodulatory effects on human monocytes/macrophages. (28th November 2017) - Talmon, Maria; Rossi, Silvia; Pastore, Anna; Cattaneo, Carlo Ignazio; Brunelleschi, Sandra; Fresu, Luigia Grazia
Abstract : Background and Purpose: A crosstalk between the immune system and depression has been postulated, with monocytes/macrophages and cytokines having a key role in this interaction. In this study, we examined whether vortioxetine, a multimodal anti‐depressive drug, was endowed with anti‐inflammatory and antioxidative activity, leading to immunomodulatory effects on human monocytes and macrophages. Experimental Approach: Human monocytes were isolated from buffy coats and used as such or differentiated into M1 and M2 macrophages. Cells were treated with vortioxetine before or after differentiation, and their responsiveness was evaluated. This included oxy‐radical and TNFα production, TNFα and PPARγ gene expression and NF‐κB translocation. Key Results: Vortioxetine significantly reduced the PMA‐induced oxidative burst in monocytes and in macrophages (M1 and M2), causing a concomitant shift of macrophages from the M1 to the M2 phenotype, demonstrated by a significant decrease in the expression of the surface marker CD86 and an increase in CD206. Moreover, treatment of monocytes with vortioxetine rendered macrophages derived from this population less sensitive to PMA, as it reduced the oxidative burst, NF‐kB translocation, TNFα release and expression while inducing PPARγ gene expression. FACS analysis showed a significant decrease in the CD14 + /CD16 + /CD86 + M1 population. Conclusions and Implications: These results demonstrate that in human monocytes/macrophages, vortioxetine has antioxidant activity and anti‐inflammatory effects driving the polarization of macrophages towards their alternative phenotype. These findings suggest that vortioxetine, alongside its antidepressive effect, may have immunomodulatory properties.